Generation of Fibrin-Based Aortic Vessels with Layer-Specific Cell Architecture Under Pulsatile Perfusion in a Clinical Organ Care System - Celina Delia Käding; Clara-Sophie Glomb; Patrick Stadler; Imke Becker; Melanie Klingenberg; Hans-Klaus Höffler; Michael Pflaum; Arjang Ruhparwar; Mathias Wilhelmi; Florian Helms (Annals of Biomedical Engineering, 2026)
Purpose Overcoming the limitations of synthetic vascular grafts in the development of biocompatible and regenerative vessels remains a long-term objective in tissue engineering. In this study, we engineered large-diameter fibrin-based vascular grafts with a target inner diameter of 21 mm replicating all three layers of the native human vessel wall in vitro. Methods The Tunica media was reconstructed using a compressed high-density (25 mg/mL) fibrin matrix seeded with smooth muscle cells expressing α-SMA and calponin, differentiated from adipose-derived mesenchymal stem cells (ASCs). The Adventitia -equivalent was formed in a 5 mg/mL fibrin gel containing ASCs, human umbilical vein endothelial cells (HUVECs), and normal human dermal fibroblasts (NHDFs) to enable the formation of a capillary-like network resembling the native adventitial Vasa vasorum . The luminal surface was endothelialized with HUVECs to replicate the Tunica intima . While controls were cultured statically for 7 days, other grafts were evaluated under pulsatile perfusion at physiological pressures using the TransMedics ® “Organ Care System Heart ™ ”. Results The stepwise fabrication technique resulted in three-layered bioartificial vessel equivalents with a mean inner diameter of 21 mm. All constructed vessels ( n = 3) maintained sufficient biomechanical stability to withstand physiological pressure (120.9 ± 1.2 to 61.4 ± 12.5 mmHg) at 60 bpm throughout the perfusion period. The aortic grafts exhibited a cyclic stretch (8.95 ± 2.03%) within the physiological range of native vessels. Mechanical stimulation induced a layer-specific physiological cell morphology and alignment across all three layers of the vascular wall. Endothelial coverage was high on static grafts (81.39 ± 2.37%) and on one of three dynamic grafts. Shear stress during perfusion (0.38 ± 0.03 dyn cm −2 ) remained below physiological levels, and further evaluation under prolonged perfusion (> 21 days) is required to assess long-term biomechanical stability and vascular functionality. Conclusion This approach may be considered a proof of concept and constitutes a first step toward the development of biometric and functional large-diameter vessel replacements.